Efeitos da paroxetina durante sessões de teste e reteste no labirinto em cruz elevado - Paiva, Izabela Lima (2022)
Anxiety and fear mediate critical fight-and-flight responses, which are essential to survival. As a pathology, anxiety is characterized by the overvaluation of potential threats and sustained worry. Such a condition strongly impacts daily life, resulting in a social dysfunction that can trigger other mood disorders such as depression and bipolar disorder. According to a World Health Organization estimative, anxiety disorders affect around 3.6% of the world population, and this number increased drastically after the COVID-19 pandemic. The elevated plus-maze (EPM) is the most used task for assessing anxiety-like behavior in rodents. This task is based on an avoidance-approach conflict generated by the natural behavior of rodents to explore a new environment and its aversion to open and light spaces. Interestingly, when the animals are re-exposed to the maze, a phenomenon called one-trial tolerance (OTT) may occur. In this phenomenon, drugs that have an anxiolytic effect when administered on the first day of EPM exposure tend not to be anxiolytic when administered on the second day. Of note, OTT has implications for translatability from preclinical research since the EPM is often used as an acute task during screening for anxiety treatments. In the present study, we investigated the effects of the systemic administration of paroxetine, a selective serotonin reuptake inhibition widely used to treat anxiety disorders, during a test (first exposure) and a retest (second exposure) session in the EPM taking place in consecutive days. Given that anxiety disorders exhibit gender differences since they are more prevalent in females, we studied cohorts of both male and female C57BL/J6 mice, which were analyzed either combined or separately. Our results show that paroxetine is indeed anxiolytic during the test session in the EPM. Nevertheless, we observed the OTT phenomenon in animals treated with vehicle in the test session and with paroxetine 24 hours later in the retest session, in which case paroxetine no longer had an anxiolytic effect. Curiously, we also found that paroxetine treatment in the first EPM session leads to a long-term anxiolytic effect; namely, animals later injected with vehicle in the retest session exhibited a lower anxietylike behavioral profile than animals treated with vehicle in both the test and retest sessions. Further experimental protocols revealed that paroxetine administered after the first EPM exposure was also associated with a long-term anxiolytic effect in the second EPM exposure 24 hours later. Most of our results held true when analyzing males and females separately, though specific sex differences in some behaviors could also be found. In all, we conclude that paroxetine has different effects during the test and retest sessions in the EPM.